A study on calculating methods of rational replacement period of heavy pepair of tractors - CHEN Kai-kao; ZHENG Wen-zhong; ZENG Ping-ou; HE Yong (浙江大学学报. 农业与生命科学版)
Index selection in calculating rational replacement period of tractors is systematically analyzed considering the law of technology state of tractors and wear and tear of spare parts and methods for calculating economic limits of both overhaul and replacement on agricultural machinery are put forward in terms of cost of unit production. Then, both optimal and rational renewal cycle under different conditions were analyzed from the viewpoint of optimizing the economical benefit of the tractors owners.